2007
DOI: 10.1086/508792
|View full text |Cite
|
Sign up to set email alerts
|

Social Status and Newspaper Readership

Abstract: In this article, the authors explore the social bases of cultural consumption by examining the association between newspaper readership and social status. They report a strong and systematic association between status and newspaper readership which is consistent with the expected link between status in the classical Weberian sense, on the one hand, and cultural level and lifestyle, on the other. This association persists in a multinomial logistic regression model in which the authors take into account, among o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 35 publications
1
72
0
5
Order By: Relevance
“…In particular, it looks at attendance at cultural performances and reading books. These two activities represent both status motivations and cognitive aspects of cultural consumption (e.g., Chan and Goldthorpe 2007a;Rössel 2011).…”
Section: Cultural Activities and Dimensionsmentioning
confidence: 99%
“…In particular, it looks at attendance at cultural performances and reading books. These two activities represent both status motivations and cognitive aspects of cultural consumption (e.g., Chan and Goldthorpe 2007a;Rössel 2011).…”
Section: Cultural Activities and Dimensionsmentioning
confidence: 99%
“…Doherty's mother reportedly 'took great pride in bringing up her children in a more middle-class environment than the one she'd enjoyed' ( To study to what extent journalists frame Amy Winehouse and Pete Doherty differently in relation to their rock and roll lifestyle, we examined two British broadsheet newspapers: The Guardian and The Independent. Since these broadsheets target -and are read by -the educated elite in high-status (non-manual professional and managerial) occupations (Chan and Goldthorpe 2007), they are likely to have a strong impact on how other media and society in general discuss a particular topic. We limit the studied period from the year Amy Winehouse (2006) respectively, were certified platinum.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on women only, previous studies have indeed shown that music critics often act more like 'men' than as journalists, representing female artists as women -instead of musicianscomparing them to other women only (Davies 2001 Second, broadsheet journalists might hold both artists accountable to transnational business masculinity, as their readers consist of, amongst others, the managerial elite (Chan and Goldthorpe 2007). Independence, authority, and self-assertiveness are important in the practice of both masculinities.…”
Section: Rock Masculinity Accountabilities and Complicit Media Pracmentioning
confidence: 99%
“…And if addressees convey shared social features, not only are their linguistic traits revealed to us, but also the sociolinguistic shifting parameters (register, diastratic and/or diaphasic traits) of the sociolect in question. A number of studies have demonstrated "a strong and systematic association between status and newspaper readership" (Chan & Goldthorpe, 2007: 1125.…”
Section: Decoding a Sociolect Through Text-samplesmentioning
confidence: 99%